PEMBINAAN MEMBUAT APLIKASI TOKO ONLINE SEBAGAI MEDIA PROMOSI PADA HOME INDUSTRY MASYARAKAT TANJUNG GUNDAP RT.02/ RW.01 - Nora Pitri Nainggolan; Intan Utnasari (ASOSIASI IDEBAHASA KEPRI, 2021)
In the midst of technological advances today there are still people who are far from technological advances. This community is a native tribe that is on the sea coast by depending on its life from the sea by becoming fishermen. One of the remaining marine tribes on the coast of Batam City is the Tanjung Gundap sea tribe. Therefore, this service is carried out in Tanjung Gundap. Tanjung Gundap is located in Riau Islands, Batam City, Kecamatan Sagulung, Kelurahan Tembesi. This service was given to the community of Tanjung Gundap in RW 01/ RT 02. The service is done by providing guidance to the community about how they can market their home industry which is snacks (kerupuk) that they have processed and can be sold more maximally by utilizing social media in order to reach consumers more broadly. Coaching is done by creating social media and online stores. The coaching was done twice. The first meeting was about the introduction of social media and online stores that can be optimally utilized for the promotion and sale of products. The second coaching is done by creating emails, social media such as facebook, instagram as well as taking online such as shopee. The coaching that has been done can increase the spirit of the community in making home industry products and market optimally.